Design and development of an autonomous robot sumo - Chew, Jing Deng. (2009)
The purpose of this project is to design and develop an autonomous sumo robot to compete in the Singapore Robotics Games 2009. This autonomous robot is a self-contained mobile robot that is able to make decisions on its own, based on the physical changes of the environment. Using its sensors and a robust algorithm, it is able to detect its enemy, act within constraints and react to their action by pushing them out of the ring.